2019
DOI: 10.5194/amt-12-5071-2019
|View full text |Cite
|
Sign up to set email alerts
|

Toward autonomous surface-based infrared remote sensing of polar clouds: retrievals of cloud optical and microphysical properties

Abstract: Abstract. Improvements to climate model results in polar regions require improved knowledge of cloud properties. Surface-based infrared (IR) radiance spectrometers have been used to retrieve cloud properties in polar regions, but measurements are sparse. Reductions in cost and power requirements to allow more widespread measurements could be aided by reducing instrument resolution. Here we explore the effects of errors and instrument resolution on cloud property retrievals from downwelling IR radiances for res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…The magnitude and spectral shape of the downwelling longwave radiance measured by the AERI from 8 to 25 µm is sensitive to cloud temperature, optical depth, thermodynamic phase, and particle effective radius. Cloud properties retrieved from AERI measurements using the Cloud and Atmospheric Radiation Retrieval Algorithm (CLARRA; Rowe et al 2019) are shown in Figs. 11g-n.…”
Section: Examples Of Representative Individual Casesmentioning
confidence: 99%
“…The magnitude and spectral shape of the downwelling longwave radiance measured by the AERI from 8 to 25 µm is sensitive to cloud temperature, optical depth, thermodynamic phase, and particle effective radius. Cloud properties retrieved from AERI measurements using the Cloud and Atmospheric Radiation Retrieval Algorithm (CLARRA; Rowe et al 2019) are shown in Figs. 11g-n.…”
Section: Examples Of Representative Individual Casesmentioning
confidence: 99%
“…5.2 TCWret vs. CLARRA Figure (10) shows the comparison of the results from TCWret and CLARRA for the cloud water optical depth τ cw , the total effective droplet radius r total and the condensed water path CW P . Although both retrievals use different coupling algorithms between LBLRTM and DISORT with different uncertainties in the spectral radiances (Rowe et al, 2019) and TCWret does not use the microwindows below 770.9 cm −1 , all retrieved quantities show a high agreement between both retrievals. Thus, retrieval results of TCWret are consistent with those from CLARRA.…”
Section: Radiance Offsetmentioning
confidence: 99%
“…Total Cloud Water retrieval (TCWret) is a retrieval for microphysical cloud parameters from FTIR spectra. It is inspired by MIXCRA (Turner, 2005), CLARRA (Rowe et al, 2019) and XTRA (Rathke and Fischer, 2000) and uses an optimal estimation approach (Rodgers, 2000) to invert the measured spectral radiances for retrieving microphysical cloud parameters. TCWret is a new software developed at the Institute of Environmental Physics (University of Bremen) and is originally designed to be applied to the dataset acquired during the PS106 and PS107.…”
Section: Cloudnet Measurementsmentioning
confidence: 99%
See 2 more Smart Citations